Anticipated Self and Public Stigma in Suicide Prevention Professionals - Roškar, Saška; Kralj, Domen; Andriessen, Karl; Krysinska, Karolina; Vinko, Matej; Podlesek, Anja (Frontiers in Psychiatry, 2022)
Background: Stigma about mental illness – both public and self – is one of the most important factors hindering help-seeking. Stigma can occur during an acute episode of mental illness or be anticipatory. One group affected by stigma, but often neglected, is mental health professionals. This study examined the anticipated form of mental-illness and help-seeking self-stigma and the anticipated form of public stigma of suicidal behavior among members of the International Association for Suicide Prevention. We hypothesized that suicidologists with a history of suicidality or mental illness would anticipate greater stigma from the public and self. Methods: The study received ethical approval from the Commission for Medical Ethics of the Republic of Slovenia. Data from 83 participants who completed an online survey (February to May 2020) with informed consent were analyzed using path analysis. We tested a model predicting help-seeking self-stigma based on (i) personal experience of mental illness using anticipated self-stigma of mental illness as a mediating variable and (ii) history of suicidal behavior using anticipated public stigma of suicidal behavior as a mediating variable. Results: Personal experience of mental illness predicted anticipation of self-stigma of mental illness (β = 0.26). History of suicidality predicted anticipation of public stigma of suicidal behavior (β = 0.29). Anticipated self-stigma of mental illness proved to be a stronger predictor of help-seeking self-stigma (β = 0.40) than anticipated public stigma of suicidal behavior (β = 0.07). Conclusions: It is important to intentionally support the mental health of suicide prevention professionals, as they are not immune to mental illness or various types of stigma. Because our sample was small and diverse, further research to better understand stigma concepts in this population is warranted.